Menelaah Peran Bina Marga dalam Meningkatkan Penerangan Jalan Publik - Muamar Fadhlillah; Dewi Noor Azijah; Cucu Sugiarti (Jurnal Ilmiah Wahana Pendidikan, 2022)
Sub-Department of Highways as part of the Office of Highways where the Sub-Department is the Office Work Unit in the implementation of Highways Department affairs in the City of Administration of East Jakarta. In carrying out these official affairs, the principle of good service must be carried out. One of the roles of the Bina Marga Sub-Department is that the Sub-Department has the task of carrying out the regulation, guidance, planning, management, development, maintenance, care, control, monitoring, evaluation, research, improvement, development and security of roads, bridges and road complementary buildings and road equipment. It is important for the East Jakarta area to highlight a face that looks good and neat. The Sub-Department of Highways has been stated in the Decree of the Governor of the Special Capital Region of Jakarta Number 111 of 2001 concerning the Organization and Work Procedure of the Public Street Lighting Service and Utility Network Facilities for the Special Capital Region of Jakarta. Where it has been regulated is the position and functions and duties of Bina Marga for the East Jakarta Region.